A Review on Ontology Languages - Revathy, R (International Journal of Computer Sciences and Engineering, 2025)
Ontology languages play key roles for representing and process info regarding the important world for the rising linguistics net. Efforts are created to develop varied metaphysics languages. Every metaphysics language provides totally different communicatory power and conjointly process quality for reasoning. Metaphysics question languages were developed to question the data outlined by these metaphysics languages and reasoning systems. We have a tendency to conduct a study to match their communicatory power, efficiency, and scalability and best performing arts scenario